Avaliação dos entraves relacionados ao processamento de leite e sua relação com a segurança alimentar dos produtores familiares no município de Piracanjuba - Goiás - Macêdo, Anna Lídia Faria (2013)
The milk productive chain stands out in the Brazilian agribusiness and the milk is an important source of income to small producers. Therefore, due to the low production scale and quality of milk these producers end up excluded from the market or having low payment per liter delivered to the dairies. In this sense, the processing of the milk into some derivative becomes a more rentable alternative to small producer. Given this situation, the question ‘how these derivatives are produced’ rises, whether or not there is the knowledge of Good Practices on Manufacturing and what is the relation with the wide Food Safety of family agribusinesses involved. The goal of this study was to detect the association between barriers related to safe food processing at the familiar agribusinesses producers of milk derivatives (food safety) and Food Safety treated broadly (food security), in the municipality of Piracanjuba - GO . This is an exploratory research, descriptive and has a quantitative and qualitative character. The sample consists of 20 small producers of milk derivatives. Six of them produce milk jam and 14 produce cheese. The research tools were a checklist for verification about Good Practices of Production (BPF), a form characterizing Food Security of producers and a supplementary questionnaire. All results were tabulated using a Microsoft Excel 2013 tool. The survey found that establishments producers of milk jam maintain the best manufacturing practices comparing to cheese producers. In general, 65 % of establishments have a high-risk rate for safety of food and 35 % have medium risk, and the final risk rating for safety of the food was level C. At Food Security evaluation, 90 % of the families studied presented food security, while 10 % presented low Food Insecurity. There is a relationship between the production of milk derivatives and food security of the family, due to the increase in family income brought by the sale of the derivatives. However, evaluating wide food security of the agribusinesses, it was found that there is no food security for these ones, because they didn’t reach the five axles that compose the wide food security: health, ecology, authenticity and solidarity. The family agribusinesses that produce milk derivatives suffer restrictions on food safety. Using other words, the food safety related to manufacturing, technological and management barriers/ training and legal and related to food security, ie, at the wide Food Security, the obstacles are related to social , environmental, hygienic and health axles .